Optimization of the Mackerel Scad Supply Chain through Sustainable Management and Technical Approaches - Umar Tangke; Sitkun Deni; Ahmad Talib; Maskhur Abdul Kadir (BIOSAINSTEK, 2026)
This study discusses the optimization of the mackerel scad supply chain in Indonesia through the implementation of data-driven management approaches, modern technology, and sustainability practices. Key challenges include overfishing, post-harvest losses, limited infrastructure, and a lack of awareness of sustainable practices. The proposed solutions encompass enhanced human resource training, the utilization of information and communication technologies, the application of cold chain systems and modern processing techniques, and strategic collaboration among stakeholders. Results indicate that these innovations can improve catch yields, product quality, global competitiveness, and resource sustainability. The main recommendations include infrastructure development, strengthened partnerships, and the integration of sustainability principles across the entire supply chain to ensure a resilient and sustainable fisheries industry in Indonesia.